2022
DOI: 10.1111/head.14354
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal hemicrania in children and adolescents: A systematic review

Abstract: BackgroundIt has been so long since a child was rst diagnosed with paroxysmal hemicrania, however, it is unknown whether children's paroxysmal hemicrania follows the same patterns as adults. We aim to report the accessible demographic, clinical and radiological characteristics of reported pediatric paroxysmal hemicrania. MethodsThis study followed the latest version of PRISMA. PubMed, Web of Science, and Scopus were searched systematically without time limitation. We included all peer-reviewed articles includi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…For PH the largest number of reported cases in a single study with a documented tobacco exposure history was 74 patients (lacked sex distribution), SUNCT and SUNA 20 patients and for HC a study of 34 patients (no sex distribution was noted) (14)(15)(16). All pediatric and adolescent investigations had no personal or secondary cigarette smoke exposure data (17)(18)(19). None of the original case descriptions for each of these unique conditions mentioned a smoking history (20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%
“…For PH the largest number of reported cases in a single study with a documented tobacco exposure history was 74 patients (lacked sex distribution), SUNCT and SUNA 20 patients and for HC a study of 34 patients (no sex distribution was noted) (14)(15)(16). All pediatric and adolescent investigations had no personal or secondary cigarette smoke exposure data (17)(18)(19). None of the original case descriptions for each of these unique conditions mentioned a smoking history (20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 summarises the published cohorts which provide the most complete information on phenotyping. The median age of onset is in the fourth decade, but the disorder can manifest in the first decade (38) and the ninth (39). Although pooling of earlier reports suggested a female predominance more recent cohorts suggest both sexes are equally affected.…”
Section: Epidemiologymentioning
confidence: 99%
“…A systematic review of 22 articles on paroxysmal hemicrania in children and adolescents reported that almost all patients benefited from acemetacin/indomethacin. Although paroxysmal hemicrania (PH) is a primary headache disorder belonging to the trigeminal autonomic cephalalgias (TACs) group, it is also reported that the pain was quite severe in the cases included in this review 22 .…”
Section: Joint Stiffnessmentioning
confidence: 99%